Influence of the hypothalamus–pituitary–gonadal axis reactivation and pubertal hormones on gray matter volume in early pubertal girls. (30th September 2021) - Zhou, Lu; Chen, Tao; Wang, Yu; Fu, Yuchuan; Xie, Xiaoling; Liu, Xiaozheng; Chen, Wei; Yan, Zhihan; Liu, Peining
Abstract: Objective: Puberty is a sensitive period of brain development accompany with pubertal hormones fluctuation. However, the underlying mechanisms of the impact of hypothalamus–pituitary–gonadal (HPG) axis reactivation and associated elevated pubertal hormones on brain structure are still unclear. Here, we investigated the brain structure differences between girls with and without HPG axis reactivation and the influence of pubertal hormones on these brain regions. Methods: 126 girls aged 8–9.5 years underwent a gonadotropin-releasing hormone (GnRH) stimulation test to identify the HPG axis status and categorized into HPG+ group ( n  = 80) and HPG- group ( n  = 46). T1-weighted gradient echo three dimensional MRI was performed using a 3.0-Tesla scanner to assess the difference in GMV between the two groups. Correlation analyses were conducted to explore the relations between the brain regions showing significant GMV differences and serum hormone concentrations. Result: The HPG+ group showed significantly higher GMV in the bilateral lingual gyrus and lower GMV within the right orbital inferior frontal gyrus compare to the HPG − group. Furthermore, GMV in the right orbital inferior frontal gyrus was positively associated with plasma concentrations of follicle stimulating hormone (FSH) in HPG+ group. Conclusion: The present study suggests that the reactivated HPG axis could affects regional structural brain changes in early pubertal girls. FSH production play an important role in bilateral lingual gyrus, which are involved in vision processing, semantic processing and emotional expression.